2019
DOI: 10.3390/cells9010020
|View full text |Cite
|
Sign up to set email alerts
|

Lights and Shadows in the Use of Mesenchymal Stem Cells in Lung Inflammation, a Poorly Investigated Topic in Cystic Fibrosis

Abstract: Mesenchymal stem cells (MSCs) are multipotent non-hematopoietic stem cells residing in many tissues, including the lung. MSCs have long been regarded as a promising tool for cell-based therapy because of their ability to replace damaged tissue by differentiating into the resident cell and repopulating the injured area. Their ability to release soluble factors and extracellular vesicles has emerged as crucial in the resolution of inflammation and injury. There is a growing literature on the use of MSCs and MSC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 150 publications
(128 reference statements)
0
10
0
Order By: Relevance
“…They also contribute to tissue regeneration, angiogenesis, and clearance of microorganisms. Indeed, the secretory and paracrine effects of MSC have continued to be extensively studied, and it is widely accepted in the MSC field that their secretome is predominantly responsible for the intercellular crosstalk between MSC and targeted cells [111][112][113].…”
Section: Mesenchymal Stromal Cells (Msc)mentioning
confidence: 99%
“…They also contribute to tissue regeneration, angiogenesis, and clearance of microorganisms. Indeed, the secretory and paracrine effects of MSC have continued to be extensively studied, and it is widely accepted in the MSC field that their secretome is predominantly responsible for the intercellular crosstalk between MSC and targeted cells [111][112][113].…”
Section: Mesenchymal Stromal Cells (Msc)mentioning
confidence: 99%
“…Our previous researches provided reliable results on the bene cial effects of MSCs on improving liver ischemia/reperfusion injury (IRI) in vivo and in vitro [10,11]. In addition, our and other several studies have also shown that MSCs could alleviate lipopolysaccharide (LPS)-induced ALI via their well-de ned roles in immunomodulation and differentiation into multiple different cell types, including adipocytes, osteoblasts and lung-related cell types [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 86%
“…Mesenchymal stem cells (MSCs) are an allogenic source of cells that have been investigated for their application in CF cell-based therapy due to their immunomodulatory and anti-inflammatory properties (reviewed in ( Caretti et al, 2019 )). In favor of their potential for CF cell therapy, MSCs co-cultured with CF immortalized airway epithelial cells at air-liquid interface have demonstrated acquisition of an epithelial phenotype, and subsequent restoration of functional CFTR protein ( Carbone et al, 2014 ; Carbone et al, 2018 ).…”
Section: Cell-based Therapiesmentioning
confidence: 99%